PENGARUH FAKTOR-FAKTOR PELATIHAN TERHADAP PRESTASI KERJA KARYAWAN DEPARTEMEN PRODUKSI PT. X BATAM - Ratnasari, Sri Langgeng (Buletin Studi Ekonomi; Vol 18, No. 1,Februari 2013. (PP 1-84), 2013)
This research objective is to find the impact of training to performance. Performance function is as a dependent variable on this research. Training functionate as independent variable. The sample of this research included fifty permanent worker in Production Departement of PT. X Batam, acquired by purposive sampling. Data is collected through questionnaire and analyzed by multiple regression analysis method by Statistical Package for the Social Sciences (SPSS.
Keywords: training and performance